Temperature-solvent dual-response information processing hydrogel with subject-object recognition and regulation effects, preparation method and application thereof
By introducing Ad groups into the PNIPAm network and using the host-guest recognition effect of β-cyclodextrin and adamantane, a temperature-solvent double-responsive composite hydrogel was constructed, which solved the PNIPAm hydrogel in room temperature and low temperature environments. The problem of insufficient information processing capabilities realizes fast response and multiple encryption/decryption functions in a wide temperature range.
Patent Information
- Application Number
- CN202411600493.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, PNIPAm hydrogel needs to be within the range of 32-40°C to achieve information encryption, which will be decrypted at room temperature, and the optical regulation behavior of solvent response is weakened under low temperature conditions, resulting in the loss of solvent-based encryption capabilities in cold environments and Temperature-sensitive information encryption capability.
The semi-interpenetrating network method is used to introduce Ad-PNIPAm with Ad group grafted into the PNIPAm network. By changing the grafting degree of Ad-MA, it regulates the kinesia water balance, and combines the host-guest recognition effect of β-cyclodextrin and adamantane. , construct a composite hydrogel with temperature and solvent dual response, expand its temperature response range and improve solvent responsiveness.
It realizes the encryption and decryption function that responds quickly under a wide range of room temperature environments (4-40℃), with adjustable encryption and decryption time, stable reversibility and multiple encryption/decryption capabilities, suitable for information entry in real life scenarios , encryption and decryption.
Smart Images

Figure CN119285996A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of intelligent response type hydrogel preparation, and particularly relates to a temperature-solvent dual response information processing hydrogel with host-guest recognition and regulation function, a preparation method and application thereof. Background Art
[0002] From ancient times to the present, information security issues have always been the focus of people's attention. In ancient times, people used methods such as Spartan encryption, Caesar cipher, and wax sealing to prevent the leakage of military, commercial, and property security information. Today, with the continuous development of information technology, people have higher and higher requirements for the security, convenience, and versatility of information encryption technology. Limited by traditional materials, the development of information processing materials with powerful information encryption / decryption functions has become a major challenge. Information entry and encryption models based on holographic anti-counterfeiting, information storage, 3D printing, and fluorescent recognition technologies have emerged.
[0003] In recent years, hydrogels have become popular candidate materials in the field of modern information encryption technology due to their unique three-dimensional network structure, good flexibility and fascinating intelligent responsiveness. Hydrogel information processing models can be divided into active-driven and passive-driven models according to different driving forces. Passive-driven refers to stimulus-responsive hydrogels that change the properties of gels due to environmental changes, such as thermochromism, natural photochromism, and hygrochromism. Active-driven refers to stimulus-responsive hydrogels that change the properties of gels due to artificial factors, such as solvatochromism, electrochromism, and fluorescence-induced chromism. Inspired by the molecular mechanisms of natural systems, natural host molecules such as α, β, and γ-cyclodextrin have been shown to affect the physical and chemical properties of polymers through supramolecular interactions with polymers. This approach of combining supramolecular chemistry with intelligent response is building a series of smart materials with unprecedented performance. For example, Yang et al. used butyl-naphthalimide with flexible ethylenediamine-functionalized β-cyclodextrin (N-CD) as a fluorescent responsive ink for printing or patterning information on a polymer brush with adamantane groups, which had bright green photoluminescence under UV light. Li et al. constructed a photoresponsive supramolecular coordination polymer (SCP) through hierarchical self-assembly of lanthanide ions, biligands, and diarylethene units, and used SCP as a security ink to print various patterns, realizing photoreversible multi-information patterns with visible / invisible transformations by simply alternating UV and visible light irradiation.
[0004] Active / passive dual-driven PNIPAm with temperature response and solvent response is undoubtedly one of the ideal materials for building information processing models. Chen et al. introduced cellulose to adjust the hydrophilic-hydrophobic balance of PNIPAm to construct an actively driven solvent-responsive hydrogel with information recording, self-encryption and multiple decryption functions at room temperature. Xue et al. used N-isopropylacrylamide, polyvinyl alcohol and octadecyl polyoxyethylene ether acrylate (SGA 15) as raw materials to develop an actively driven solvent-responsive hydrogel with high resolution, repeatable recording and strong information encryption / decryption capabilities. However, there are two problems when PNIPAm hydrogel is used as an information processing model. First, PNIPAm hydrogel needs to be in the range of 32-40℃ to achieve information encryption and decryption will occur at room temperature. Obviously, such conditions are not suitable for real application scenarios. Secondly, under low temperature conditions (4℃), the optical regulation behavior of PNIPAm hydrogel solvent response is significantly weakened, which makes PNIPAm hydrogel in cold environment lose both solvent encryption ability and temperature-sensitive information encryption ability. In order to make PNIPAm hydrogel more adaptable to application requirements and broaden its phase transition temperature range, researchers have adopted various strategies to adjust its thermal response properties, including copolymerization, composite method or addition of inorganic salts. Takei et al. introduced hydrophobic butyl methacrylate (BMA) into NIPAm through free radical reaction to reduce the LCST of hydrogel. With the increase of BMA composition, LCST dropped to below 32 °C. The poly (N-isopropylacrylamide-co-N-maleyl gelatin) [P (NIPAAm-co-N-MAGEL)] hydrogel prepared by Xin et al. + Mg 2+ and Al 3+ concentration shows a linear dependence and can be observed in Al 3+ The transparency of the hydrogel is regulated and the formation of double network (DN) hydrogel is induced under the action of the hydrogel. In fact, such examples of regulating gel properties by introducing inorganic salts to provide supramolecular interactions are common. Surfactants, inorganic salts, polymer topological structure modification and the introduction of host-guest molecules can all regulate gel properties through supramolecular interactions. Therefore, it is of great significance to seek a simple design scheme to realize the information processing model of PNIPAm with information input, encryption and decryption functions at room temperature and low temperature environments. Summary of the invention
[0005] The purpose of the present invention is to provide a temperature-solvent dual-responsive information processing hydrogel with host-guest recognition and regulation function. This composite hydrogel has optically adjustable behavior that is sensitive to temperature and solvent stimulation under a wide range of room temperature environments (4-40°C). It can not only respond quickly to external stimuli in a shorter time, but also has adjustable encryption and decryption time, stable reversibility and multiple encryption / decryption capabilities.
[0006] The present invention also provides a method for preparing a temperature-solvent dual-response information processing hydrogel with host-guest recognition and regulation function.
[0007] The technical solution adopted by the present invention to solve the technical problem is:
[0008] A method for preparing a temperature-solvent dual-responsive information processing hydrogel (Ad-PNIPAmgel) with host-guest recognition regulation function, the method comprising the following steps:
[0009] S1. Synthesis of Ad-PNIPAm: N-isopropylacrylamide (NIPAM), 2,2-azobisisobutyronitrile (AIBN) and 2-methyl-2-adamantyl methacrylate (Ad-MA) were mixed in solvent 1, with a molar ratio of Ad-MA to NIPAM being 1%-8%, and the mixture was flushed with nitrogen and stirred at 60°C±5°C for 20h-24h under a nitrogen atmosphere. Subsequently, solvent 2 was added to the above solution, and the mixture was stirred at 50°C±5°C until crystals precipitated, and filtered while hot to obtain white powdered Ad-PNIPAm; the crystallization process was repeated to purify the product; and finally, the purified Ad-PNIPAm was vacuum dried at 55°C±5°C for 24h-30h;
[0010] S2. Preparation of Ad-PNIPAm gel: At 5°C, Ad-PNIPAm and NIPAM were fully dissolved in water, and appropriate amounts of N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) were added, and stirred vigorously to form a uniform solution. Tetramethylethylenediamine (TEMED) was added to the above solution and mixed evenly. The solution was allowed to stand for crosslinking for more than 24 hours at a temperature range of 0 to 4°C to obtain a semi-interpenetrating composite hydrogel Ad-PNIPAm gel, which was stored at 4°C.
[0011] S3. Ad-PNIPAm gel / β-CD based on host-guest recognition: Multifunctional Ad-PNIPAm gel / β-CD was prepared through the host-guest recognition between β-CD and Ad;
[0012] The Ad-PNIPAm gel was immersed in a β-cyclodextrin (β-CD) solution for 8 h to 9 h, and the formed composite hydrogel was taken out and dialyzed to remove the free β-CD in the composite hydrogel to obtain pure Ad-PNIPAm gel / β-CD.
[0013] Preferably, the molar ratio of Ad-MA to NIPAM in S1 is 1%-5%. Experiments have shown that 1% Ad-PNIPAm gel, 3% Ad-PNIPAm gel and 5% Ad-PNIPAm gel can achieve information encryption at 19-34°C (transmittance <1%), and complete decryption at 4°C. Preferably, the molar ratio of NIPAM, AIBN and Ad-MA described in S1 is 80mmol: 0.24mmol: 0.8mmol~4.0mmol. More preferably, the molar ratio of NIPAM, AIBN and Ad-MA is 80mmol: 0.24mmol: 4.0mmol. At this time, when the theoretical grafting degree of the Ad group is 5%, the response temperature of Ad-PNIPAm gel is the lowest, and the self-encryption process can be completed at 19°C (650nm wavelength, transmittance <1%, time <1min), and the self-decryption process can be completed at 4°C (650nm wavelength, transmittance>75%, time <5min). The encryption time is less than 1 min under the induction of anhydrous ethanol (650 nm wavelength, transmittance 78%→0.1%).
[0014] Preferably, the mass ratio of Ad-PNIPAm to NIPAM in S2 is 1:0.2 to 1:0.5.
[0015] Preferably, the mass ratio of Ad-PNIPAm to MBA and TEMED in S2 is 2:0.05:0.04 to 2:0.2:0.16; the mass ratio of MBA to APS is 3:1.
[0016] Preferably, the mass concentration of the β-CD solution in S3 is 1.0% to 4.0%.
[0017] Preferably, the dialysis condition in S3 is: dialysis in deionized water for 48 hours in a dialysis bag with a molecular weight cutoff of 8000.
[0018] Preferably, solvent 1 and solvent 2 are independently selected from one or more of tetrahydrofuran, n-hexane, and diethyl ether. Preferably, solvent 1 is tetrahydrofuran (THF), and solvent 2 is n-hexane.
[0019] A temperature-solvent dual-responsive information processing hydrogel (Ad-PNIPAm gel) prepared by the preparation method.
[0020] A temperature-solvent dual-responsive information processing hydrogel with host-guest recognition regulation is used in information encryption and decryption technology. In particular, it has optically adjustable behavior with sensitive temperature and solvent stimulation under a wide range of room temperature environments (4-40°C). The phase transition temperature of the system can be reduced to a range of 4 to 24°C, making it more suitable for real-life scenarios.
[0021] Preferably, in the application, the temperature-solvent dual-response information processing hydrogel is immersed in an ethanol solution with a volume percentage of 75% or more, including anhydrous ethanol, so that it completes the response behavior from transparent-opaque-transparent, thereby realizing the regulation of the encryption and decryption process of the composite hydrogel. In the ethanol solutions with a volume percentage of 75% and 100%, the composite hydrogel can well complete its response behavior process from transparent-opaque-transparent, and the time to complete the response behavior in the ethanol solution with a volume percentage of 75% is longer.
[0022] Preferably, in the application, the temperature-solvent dual-response information processing hydrogel is immersed in DMSO, MeOH or EG to complete the response behavior from transparent-opaque-transparent. DMSO, MeOH and EG, which are miscible with water and can form hydrogen bonds, can induce the hydrogel to produce transparent-opaque-transparent optical transition behavior, and the optical change process of transparent-opaque-transparent can also occur in water bath again, thereby realizing the regulation of the encryption and decryption process of the composite hydrogel.
[0023] Preferably, the application includes using the temperature-solvent dual-response information processing hydrogel to prepare an information processing hydrogel model device for host-guest recognition regulation, and giving it dynamic information storage and encryption / decryption functions.
[0024] The present invention uses 2-methyl-2-adamantyl methacrylate (Ad-MA) and N-isopropylacrylamide (NIPAM) as raw materials under the catalysis of 2,2-azobisisobutyronitrile (AIBN) to construct a poly-N-isopropylacrylamide derivative (Ad-PNIPAm) grafted with adamantane (Ad) group. Then, under the auxiliary polymerization and chemical crosslinking of NIPAM, a semi-interpenetrating network composite hydrogel (Ad-PNIPAm gel) is constructed. The hydrophilic-hydrophobic balance of Ad-PNIPAm is regulated by changing the grafting degree of Ad-MA in Ad-PNIPAm to adjust the stimulus response performance of Ad-PNIPAm gel. The present invention explores the influence of different concentrations of ethanol and organic solvents such as dichloromethane, ethyl acetate and ethylene glycol on the encryption and decryption process of the composite hydrogel through temperature and solvent driving. Furthermore, by introducing the host-guest recognition effect of β-cyclodextrin (β-CD) and adamantane, the hydrophilic-hydrophobic balance of the composite hydrogel network was regulated to achieve its reversible and controllable dynamic response, and its application effect as an information processing hydrogel model device was explored.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention adopts a semi-interpenetrating network method to introduce Ad-PNIPAm grafted with Ad groups into a PNIPAm network, and prepares a composite hydrogel with high resolution and active / passive dual-driven encryption and decryption functions. The synthesized composite hydrogel has sensitive optically adjustable behavior of temperature and solvent stimulation under a wide range of room temperature environments (4-40° C.). It can not only respond quickly to external stimuli in a shorter time, but also has adjustable encryption and decryption time, stable reversibility and multiple encryption / decryption capabilities. The addition of adamantane molecules can adjust the thermal response characteristics of the composite hydrogel, so that it can also show excellent solvent responsiveness under low temperature conditions. This not only has no effect on the information input, self-encryption / decryption and self-erasing functions of the composite hydrogel, but also has higher resolution. Therefore, under the stimulation of anhydrous ethanol, the composite hydrogel can show a transparent-opaque-transparent self-encryption and self-decryption process. At the same time, not only can the encryption and decryption process be controlled by controlling the ethanol concentration and solvent type, but also by introducing the host-guest recognition effect of β-cyclodextrin and adamantane, the information confidentiality time of the composite hydrogel can be maximized and the information encryption and decryption process can be regulated.
[0027] Compared with traditional PNIPAm hydrogels, this material has a wider temperature response range and a higher solvent response threshold, and can realize information entry, encryption and decryption at low temperatures, making PNIPAm hydrogel information processing models more suitable for real-life scenarios and enabling them to be widely used in the field of encryption / decryption. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The synthesis route and structural characterization of the linear polymer Ad-PNIPAm (a) 1HNMR spectrum and synthesis route; (b) 1HNMR spectrum 1.3-2.5ppm enlarged view; (c) FT-IR spectrum; (d) FT-IR spectrum 1000-1800cm-1 enlarged view;
[0029] Figure 2 (a) The actual picture of the transparent-opaque-transparent optical change of Ad-PNIPAm gel in ethanol and water environment at 4°C; (b) The transmittance change curve of Ad-PNIPAm gel in anhydrous ethanol; (c) The transmittance change curve of Ad-PNIPAm gel after it was put back into the water bath over time;
[0030] Figure 3 (a) The pore structure change of 5% Ad-PNIPAm gel during solvent-induced optical change; (b) Schematic diagram of the mechanism of solvent-induced optically tunable behavior of hydrogels;
[0031] Figure 4 (a) Optical changes of 5% Ad-PNIPAm gel in ethanol solutions of different concentrations at 4°C; (b) Transmittance changes of 5% Ad-PNIPAm gel in DCM, EA, EG, DMSO, MeOH and n-Hexane;
[0032] Figure 5 Rheological and optical properties of composite hydrogels as a function of temperature: (a) storage modulus G' and loss modulus G"; (b) apparent viscosity η*; (c) transmittance;
[0033] Figure 6 (a) A physical picture of the composite hydrogel changing with temperature; (b) A schematic diagram of the mechanism of temperature-responsive hydrogel optical regulation behavior;
[0034] Figure 7 (a) FT-IR spectrum of Ad-PNIPAm gel / β-CD after immersion in β-CD solution; (b) FT-IR spectrum of Ad-PNIPAm gel / β-CD after removal of free β-CD; (c) G' and G" of Ad-PNIPAm gel / β-CD changing with temperature; (d) temperature scanning comparison of composite hydrogel before and after host-guest recognition; (e) host-guest recognition mechanism diagram of Ad-PNIPAm gel / β-CD regulating response behavior;
[0035] Figure 8(a) Comparison diagram of the temperature response encryption process of 5% Ad-PNIPAm gel / β-CD and 5% Ad-PNIPAm gel; (b) Comparison diagram of the self-encryption and decryption process of 5% Ad-PNIPAm gel / β-CD and 5% Ad-PNIPAm gel in ethanol. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.
[0037] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0038] The reagents used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent stores.
[0039] The 100% ethanol solution described in the present invention refers to anhydrous ethanol.
[0040] The Ad-PNIPAm of the present invention is tested for its element content by an element analyzer, and its grafting degree (GD) is calculated by the following formula (1).
[0041]
[0042] Among them, α is the content ratio of N / C, M C and M N are the relative atomic masses of C and N respectively.
[0043] The Ad-PNIPAm of the present invention is prepared by FT-IR and 1 Its molecular structure was detected by H NMR.
[0044] Ad-PNIPAm gel and Ad-PNIPAm gel / β-CD described in the present invention are tested for their light transmittance by UV-visible spectrophotometer. The composite hydrogel is cut into long strip samples with length, width and height of 20 mm, 10 mm and 1 mm respectively, so that it can be loaded into the test cuvette of the UV-visible spectrophotometer. Subsequently, the treated composite hydrogel sample is placed in the cuvette, and the remaining space is filled with a solvent that can induce the reversible dynamic response of the composite hydrogel. Finally, the absorbance value (A) of the composite hydrogel is tested at a wavelength of 650 nm by a U-3900 UV-visible spectrophotometer (Hitachi, Japan), and its corresponding transmittance (T) is calculated by the following formula (2).
[0045] T = 10-A × 100% (2)
[0046] The rheological properties of Ad-PNIPAm gel and Ad-PNIPAm gel / β-CD described in the present invention were investigated using a HAAKE MARS40 rheometer (Thermo Fisher Scientific, USA). The composite hydrogel was processed into a circular hydrogel with a bottom diameter of 23 mm and a height of 1 mm, and a P20 / Ti-01161424 parallel plate fixture was used to maintain a gap of 1 mm for rheological testing. In view of the fact that the composite hydrogel has a certain temperature responsiveness, in order to avoid the influence of temperature increase on the mechanical properties of the composite hydrogel, the dynamic rheological test experiment needs to be carried out at 4°C. First, the frequency was fixed at 1 Hz, the strain was scanned from 0.1% to 100%, and the storage modulus (G') and energy loss modulus (G") were recorded to determine the linear viscoelastic region (LVR) of the composite hydrogel. Subsequently, an amplitude strain of 1% was selected within the LVR, and the frequency of the composite hydrogel was scanned in the angular frequency range of 0.1-104.8 rad / s, and G' and G" were recorded. Finally, the temperature scanning program was set to a fixed strain value of 1% and a fixed frequency of 1 Hz. The temperature scanning test was carried out in the temperature range of 4-40 °C at a heating rate of 3 °C / min, and G', G" and apparent viscosity (η*) were recorded.
[0047] The Ad-PNIPAm gel described in the present invention adopts the following method to carry out anhydrous ethanol-induced reversible dynamic response test. The prepared circular Ad-PNIPAm gel with a diameter of 23 mm and a height of 1 mm is immersed in 50 mL of anhydrous ethanol solution, and the transition process of the composite hydrogel from transparent to white opaque and then to transparent is observed and the color change time is recorded to test its solvent response characteristics. Subsequently, the composite hydrogel is taken out from the anhydrous ethanol solution, and after removing the residual ethanol on its surface with filter paper, it is immersed in 50 mL of deionized water, and its transition process from transparent to white opaque and then to transparent is observed and the corresponding color change time and transmittance are recorded. Repeat the above process 3 times to verify the reversible dynamic responsiveness of Ad-PNIPAm gel.
[0048] The composite hydrogel described in the present invention adopts the following method to carry out temperature-induced reversible dynamic response test. The prepared circular composite hydrogel with a diameter of 23 mm and a height of 1 mm is placed in a water bath prepared in advance at 4, 9, 14, 19, 24, 29, 34 and 40°C, kept for 3 minutes, and the color change of the composite hydrogel is observed and recorded. Subsequently, the composite hydrogel taken out of the 40°C water is placed in 4°C deionized water again to observe the transition time of the composite hydrogel from white opaque to transparent, thereby verifying the reversible temperature dynamic responsiveness of the composite hydrogel. At the same time, the change of the transmittance of the composite hydrogel with temperature was also explored using a UV-visible spectrophotometer.
[0049] The core technology of the present invention is to protect a preparation method of a temperature-solvent dual-responsive information processing hydrogel (Ad-PNIPAmgel), which comprises the following steps:
[0050] S1. Synthesis of Ad-PNIPAm: NIPAM, AIBN and Ad-MA were dissolved in a 250mL three-necked flask containing 80mL tetrahydrofuran (THF) according to a certain molar ratio, flushed with nitrogen for 30min, and stirred at 60°C for 20h under a nitrogen atmosphere. Subsequently, 400mL of n-hexane was added to the above solution and stirred at 50°C for 10min to precipitate crystals, followed by hot filtration to obtain white powdery Ad-PNIPAm. The above n-hexane recrystallization process was repeated three times to purify the product. Finally, the purified Ad-PNIPAm was vacuum dried at 55°C for 24h. In the present invention, the products prepared when the NIPAM and Ad-MA feed molar ratios were 1%, 3% and 5%, respectively, were marked as 1% Ad-PNIPAm, 3% Ad-PNIPAm, and 5% Ad-PNIPAm, respectively.
[0051] S2, Preparation of Ad-PNIPAm gel: At 5°C, 2gAd-PNIPAm and a certain amount of NIPAM were fully dissolved in 20mL deionized water in turn. Then, a certain amount of MBA and APS were added and stirred vigorously for 20min to form a uniform solution. Finally, a certain amount of TEMED was added to the above solution and mixed evenly, and then it was quickly transferred to a 12-well plate. 1.5mL of the mixed solution was transferred to each well, and it was allowed to stand for crosslinking at 4°C for 24h to form Ad-PNIPAm gel. The obtained Ad-PNIPAm gel has different degrees of temperature responsiveness, so it needs to be stored at 4°C. The semi-interpenetrating composite hydrogels prepared by chemical crosslinking of 1% Ad-PNIPAm, 3% Ad-PNIPAm and 5% Ad-PNIPAm were named 1% Ad-PNIPAm gel, 3% Ad-PNIPAm gel and 5% Ad-PNIPAm gel.
[0052] S3. Ad-PNIPAm gel / β-CD constructed based on host-guest recognition: Multifunctional Ad-PNIPAm gel / β-CD was prepared through the host-guest recognition between β-CD and Ad. Ad-PNIPAm gel was soaked in 50mL of β-CD solution of a certain mass concentration for 8h. Then the formed composite hydrogel was taken out and placed in a dialysis bag with a molecular weight cutoff of 8000. It was dialyzed in deionized water for 48h to remove the free β-CD in the composite hydrogel, thereby obtaining pure Ad-PNIPAm gel / β-CD. For comparison, the composite hydrogels prepared by complexing β-CD with 1% Ad-PNIPAm gel, 3% Ad-PNIPAm gel and 5% Ad-PNIPAm gel were named 1% Ad-PNIPAm gel / β-CD, 3% Ad-PNIPAm gel / β-CD and 5% Ad-PNIPAm gel / β-CD, respectively.
[0053] Example 1
[0054] 9.04g (80mmol) NIPAM, 39.6mg (0.24mmol) AIBN and 187.5mg (0.8mmol) Ad-MA were dissolved in a 250mL three-necked bottle containing 80mL THF, flushed with nitrogen for 30min, and stirred at 60°C for 20h under a nitrogen atmosphere. Subsequently, 400mL n-hexane was added to the above solution, stirred at 50°C for 10min, thereby precipitating crystals, followed by hot filtration to obtain white powdery Ad-PNIPAm. The above n-hexane recrystallization process was repeated three times to purify the product. Finally, the purified 1% Ad-PNIPAm was vacuum dried at 55°C for 24h.
[0055] Furthermore, at 5°C, 2gAd-PNIPAm and 600mgNIPAM were fully dissolved in 20mL deionized water in turn. Then, 100mg MBA and 34mgAPS were added and stirred vigorously for 20min to form a uniform solution. Finally, 80mg TEMED was added to the above solution and mixed evenly, and then it was quickly transferred to a 12-well plate. 1.5mL of the mixed solution was transferred to each well, and at 4°C, it was allowed to crosslink for 24h to form a 1% Ad-PNIPAm gel with a semi-interpenetrating network structure. The resulting 1% Ad-PNIPAm gel has different degrees of temperature responsiveness, so it needs to be stored at 4°C.
[0056] Finally, the multifunctional Ad-PNIPAm gel / β-CD was prepared through the host-guest recognition between β-CD and Ad. The Ad-PNIPAm gel was soaked in 50 mL of β-CD solution with a mass concentration of 2.5% for 8 hours. Then, the formed composite hydrogel was taken out and placed in a dialysis bag with a molecular weight cutoff of 8000. It was dialyzed in deionized water for 48 hours to remove the free β-CD in the composite hydrogel and obtain pure 1% Ad-PNIPAm gel / β-CD.
[0057] The test results show that the Ad grafting degree of 1% Ad-PNIPAm is 1.10%. The prepared composite hydrogel has good pore structure and mechanical properties, sensitive solvent and temperature stimulus responsiveness, high resolution, and inducible reversible information recording, self-encryption and decryption functions. The addition of Ad groups can adjust the thermal response characteristics of the composite hydrogel, so that it can also show excellent solvent responsiveness under low temperature conditions. It not only has no effect on the information input, self-encryption / decryption and self-erasing functions of the composite hydrogel, but also has higher resolution. Under the stimulation of anhydrous ethanol, the composite hydrogel exhibits a transparent-opaque-transparent self-encryption and self-decryption process. Finally, not only can the encryption and decryption process be controlled by controlling the ethanol concentration and solvent type, but also by introducing the host-guest recognition effect of β-cyclodextrin and adamantane, the information confidentiality time of the composite hydrogel can be extended to the greatest extent, and the information encryption and decryption process can be regulated. Therefore, this composite hydrogel with multiple regulation and multi-response based on PNIPAm has great application potential in the field of information writing and encryption / decryption.
[0058] Example 2
[0059] 9.04g (80mmol) NIPAM, 39.6mg (0.24mmol) AIBN and 560mg (2.4mmol) Ad-MA were dissolved in a 250mL three-necked bottle containing 80mL THF, flushed with nitrogen for 30min, and stirred at 60°C for 20h under a nitrogen atmosphere. Subsequently, 400mL n-hexane was added to the above solution, stirred at 50°C for 10min, thereby precipitating crystals, followed by hot filtration to obtain white powdery Ad-PNIPAm. The above n-hexane recrystallization process was repeated three times to purify the product. Finally, the purified 3% Ad-PNIPAm was vacuum dried at 55°C for 24h.
[0060] Furthermore, at 5°C, 2gAd-PNIPAm and 800mgNIPAM were fully dissolved in 20mL deionized water in turn. Then, 150mg MBA and 50mgAPS were added and stirred vigorously for 20min to form a uniform solution. Finally, 100mg TEMED was added to the above solution and mixed evenly, and then it was quickly transferred to a 12-well plate. 1.5mL of the mixed solution was transferred to each well, and at 4°C, it was allowed to crosslink for 24h to form a 3% Ad-PNIPAm gel with a semi-interpenetrating network structure. The resulting 3% Ad-PNIPAmgel has different degrees of temperature responsiveness, so it needs to be stored at 4°C.
[0061] Finally, the multifunctional Ad-PNIPAm gel / β-CD was prepared through the host-guest recognition between β-CD and Ad. The Ad-PNIPAm gel was soaked in 50 mL of β-CD solution with a mass concentration of 3.0% for 8 hours. Then, the formed composite hydrogel was taken out and placed in a dialysis bag with a molecular weight cutoff of 8000. It was dialyzed in deionized water for 48 hours to remove the free β-CD in the composite hydrogel and obtain pure 3% Ad-PNIPAm gel / β-CD.
[0062] The test results show that the Ad grafting degree of 3% Ad-PNIPAm is 2.83%. The prepared composite hydrogel has good pore structure and mechanical properties, sensitive solvent and temperature stimulus responsiveness, high resolution, and inducible reversible information recording, self-encryption and decryption functions. The addition of Ad groups can adjust the thermal response characteristics of the composite hydrogel, so that it can also show excellent solvent responsiveness under low temperature conditions. It not only has no effect on the information input, self-encryption / decryption and self-erasing functions of the composite hydrogel, but also has higher resolution. Under the stimulation of anhydrous ethanol, the composite hydrogel exhibits a transparent-opaque-transparent self-encryption and self-decryption process. Finally, not only can the encryption and decryption process be controlled by controlling the ethanol concentration and solvent type, but also by introducing the host-guest recognition effect of β-cyclodextrin and adamantane, the information confidentiality time of the composite hydrogel can be maximized, and its information encryption and decryption process can be regulated. Therefore, this composite hydrogel with multiple regulation and multi-response based on PNIPAm has great application potential in the field of information writing and encryption / decryption.
[0063] Example 3
[0064] 9.04g (80mmol) NIPAM, 39.6mg (0.24mmol) AIBN and 937.36mg (4.0mmol) Ad-MA were dissolved in a 250mL three-necked bottle containing 80mL THF, flushed with nitrogen for 30min, and stirred at 60°C for 20h under a nitrogen atmosphere. Subsequently, 400mL n-hexane was added to the above solution, stirred at 50°C for 10min, thereby precipitating crystals, followed by hot filtration to obtain white powdery Ad-PNIPAm. The above n-hexane recrystallization process was repeated three times to purify the product. Finally, the purified 5% Ad-PNIPAm was vacuum dried at 55°C for 24h.
[0065] Furthermore, at 5°C, 2gAd-PNIPAm and 1000mgNIPAM were fully dissolved in 20mL deionized water in turn. Then, 200mgMBA and 67mgAPS were added and stirred vigorously for 20min to form a uniform solution. Finally, 120mgTEMED was added to the above solution and mixed evenly, and then it was quickly transferred to a 12-well plate. 1.5mL of the mixed solution was transferred to each well, and at 4°C, it was allowed to crosslink for 24h to form a 5%Ad-PNIPAm gel with a semi-interpenetrating network structure. The resulting 5%Ad-PNIPAmgel has different degrees of temperature responsiveness, so it needs to be stored at 4°C.
[0066] Finally, the multifunctional Ad-PNIPAm gel / β-CD was prepared through the host-guest recognition between β-CD and Ad. The Ad-PNIPAm gel was soaked in 50 mL of β-CD solution with a mass concentration of 4.0% for 8 hours. Then, the formed composite hydrogel was taken out and placed in a dialysis bag with a molecular weight cutoff of 8000. It was dialyzed in deionized water for 48 hours to remove the free β-CD in the composite hydrogel and obtain pure 5% Ad-PNIPAm gel / β-CD.
[0067] The test results show that the Ad grafting degree of 5% Ad-PNIPAm is 5.00%. The prepared composite hydrogel has good pore structure and mechanical properties, sensitive solvent and temperature stimulus responsiveness, high resolution, and inducible reversible information recording, self-encryption and decryption functions. The addition of Ad groups can adjust the thermal response characteristics of the composite hydrogel, so that it can also show excellent solvent responsiveness under low temperature conditions. It not only has no effect on the information input, self-encryption / decryption and self-erasing functions of the composite hydrogel, but also has higher resolution. Under the stimulation of anhydrous ethanol, the composite hydrogel exhibits a transparent-opaque-transparent self-encryption and self-decryption process. Finally, not only can the encryption and decryption process be controlled by controlling the ethanol concentration and solvent type, but also by introducing the host-guest recognition effect of β-cyclodextrin and adamantane, the information confidentiality time of the composite hydrogel can be extended to the greatest extent, and the information encryption and decryption process can be regulated. Therefore, this composite hydrogel with multiple regulation and multi-response based on PNIPAm has great application potential in the field of information writing and encryption / decryption.
[0068] Test results and analysis
[0069] Figure 1 The synthesis route and structural characterization of the linear polymer Ad-PNIPAm: (a) 1HNMR spectrum and synthesis route; (b) 1HNMR spectrum 1.3-2.5ppm magnified image; (c) FT-IR spectrum; (d) FT-IR spectrum 1000-1800cm-1 magnified image.
[0070] The 1H NMR spectra of the raw materials NIPAm and Ad-MA and the products PNIPAm, 1% Ad-PNIPAm, 3% Ad-PNIPAm and 5% Ad-PNIPAm are shown in Figure 1 As shown in a. It can be seen that PNIPAm, 1% Ad-PNIPAm, 3% Ad-PNIPAm and 5% Ad-PNIPAm all show proton signal peaks of the methyl and methyl groups in the isopropyl group in the range of 4.00-1.14 ppm, and their broad peaks in the range of 1.5-2.5 ppm can be attributed to the proton peaks of the PNIPAM skeleton, indicating that the polymerization reaction has successfully occurred. Figure 1From the local magnified image in the range of b1.3-2.5ppm, it can be observed that 1% Ad-PNIPAm, 3% Ad-PNIPAm and 5% Ad-PNIPAm exhibited the proton peaks of -CH and -CH2 of the grafted Ad-MA at 1.59, 1.69 and 1.79ppm, respectively, and the peak intensity increased with the increase of the Ad-MA grafting degree. Figure 1 The FT-IR spectrum of c shows that NIPAm is at 1620 cm -1 The characteristic absorption peak of C=C stretching vibration at 1% Ad-PNIPAm, 3% Ad-PNIPAm and 5% Ad-PNIPAm has disappeared in the FT-IR spectra, which directly confirms the occurrence of polymerization. At the same time, their characteristic absorption peaks at 1550, 1656 and 3307 cm-1 correspond to the vibration absorption peaks of amide (-CONH-), carbonyl (CO) and NH bond, respectively. Figure 1 d The locally enlarged FT-IR spectrum shows that 1% Ad-PNIPAm, 3% Ad-PNIPAm and 5% Ad-PNIPAm show the C=O, CO and CC stretching vibration absorption peaks of the Ad-MA side group at 1716, 1213, 1103 and 1092 cm-1, respectively, while these characteristic peaks do not appear in PNIPAm, indicating that Ad-MA is grafted onto the Ad-PNIPAm molecular chain through copolymerization.
[0071] Figure 2 (a) The actual picture of the transparent-opaque-transparent optical changes of Ad-PNIPAm gel in ethanol and water environment at 4°C; (b) The transmittance change curve of Ad-PNIPAm gel in anhydrous ethanol; (c) The transmittance change curve of Ad-PNIPAm gel after being put back into the water bath over time. Figure 3 (a) The pore structure change of 5% Ad-PNIPAm gel during solvent-induced optical change; (b) Schematic diagram of the mechanism of solvent-induced optically tunable behavior of hydrogel.
[0072] like Figure 2 As shown in a, the solvent-induced optically tunable behavior of Ad-PNIPAm gel shows a change process from transparent-opaque-transparent. Figure 3As shown in b, the main reasons for the transition of the composite hydrogel from transparent to opaque are the following two points. First, the change in osmotic pressure. When the composite hydrogel is exposed to a large amount of anhydrous ethanol solution, the osmotic pressure inside and outside is different, and a large amount of anhydrous ethanol flows into the composite hydrogel. However, the diffusion rate of water molecules is much lower than the average association time of hydrogen bonds, resulting in the inability of water molecules to diffuse instantaneously and cause light scattering. Second, the change in hydrogen bonds. The entry of anhydrous ethanol causes the hydrogen bonds formed between water molecules and the composite hydrogel skeleton molecular chains to break. The formation of new hydrogen bonds between ethanol and the composite hydrogel skeleton molecular chains will inevitably cause changes in the molecular chain state and thus cause changes in color. The change from opaque to transparent of the composite hydrogel is mainly caused by the gradual balance of internal and external osmotic pressures and the stabilization of the molecular chain state. The 5% Ad-PNIPAm gel with water as the solvent has a loose and porous pore structure. With the infiltration of ethanol, its pore structure gradually becomes tight and smooth. As shown Figure 3 As shown in a, the dynamic process of the composite hydrogel pore change can be seen, and its loose and porous structure gradually becomes compact and smooth with the entry of ethanol. The composite hydrogel that has reached equilibrium in anhydrous ethanol is transferred back into water, and solvent replacement (ethanol-water) occurs, causing it to recover from a compact and smooth structure to a loose and porous structure. Figure 2 b is a graph showing the change in transmittance of the composite hydrogel at a wavelength of 650nm over time under the induction of anhydrous ethanol. The transmittance of PNIPAm gel with a single network structure is poor, and the transmittance is only 50% without solvent induction, while Ad-PNIPAm gel with a semi-interpenetrating network structure has better transmittance. The transmittance of 1% Ad-PNIPAm gel and 3% Ad-PNIPAm gel is about 62%, while 5% Ad-PNIPAm gel has the best transmittance of about 78%. After being immersed in anhydrous ethanol for 40 minutes, the transmittance of PNIPAm gel dropped to the lowest (about 25%), while the transmittance of 1% Ad-PNIPAm gel, 3% Ad-PNIPAm gel and 5% Ad-PNIPAm gel dropped to below 1% after being immersed in anhydrous ethanol for 5 minutes, showing sensitive solvent response characteristics. It is worth mentioning that during the entire solvent induction process, 5% Ad-PNIPAm gel took the longest time to complete the change (about 70 min) and had the largest range of transmittance changes (78%→0.3%→84%), while PNIPAm gel had the smallest range of transmittance changes (50%→26%→73%). Figure 2As shown in Figure c, due to the solvent effect, the composite hydrogel completes solvent replacement in deionized water (ethanol → water), and a transparent-opaque-transparent optical change occurs. Finally, the transmittance of PNIPAm gel, 1% Ad-PNIPAm gel, 3% Ad-PNIPAm gel and 5% Ad-PNIPAm gel is restored to 72%, 72%, 60% and 75%, respectively. Similar to the process of ethanol-induced optical changes, the time required for the composite hydrogel to recover transparency in deionized water increases with the increase of Ad-MA grafting degree. The above experimental results prove that the content of hydrophobic groups is one of the main reasons affecting the solvent response characteristics of composite hydrogels. Among them, PNIPAm gel contains the least hydrophobic groups (only isopropyl groups), and its water molecules diffuse faster, so it has a smaller difference with the hydrogen bond association time, and the light scattering intensity caused is smaller, which has less effect on the transmittance of the composite hydrogel, resulting in a shorter solvent replacement time. The 5% Ad-PNIPAm gel contains the most hydrophobic groups (isopropyl and adamantane groups), which form more hydrophobic areas, causing water molecules to diffuse more slowly, resulting in a greater light scattering intensity, which increases the impact on transmittance. The larger steric hindrance of the adamantane molecules may also hinder the association of hydrogen bonds, so its solvent replacement takes the longest time.
[0073] Figure 4 (a) Optical changes of 5% Ad-PNIPAm gel in ethanol solutions of different concentrations at 4°C; (b) Transmittance changes of 5% Ad-PNIPAm gel in DCM, EA, EG, DMSO, MeOH and n-Hexane.
[0074] The 5% Ad-PNIPAm gel was immersed in 5%, 25%, 50%, 75% and 100% ethanol solutions by volume to study the optically tunable behavior of the hydrogel induced by different concentrations of ethanol. Figure 4As shown in a, in 75% and 100% ethanol solutions by volume, the composite hydrogel can well complete its response behavior process from transparent-opaque-transparent, and the time to complete the response behavior in the 75% ethanol solution by volume is longer. This may be due to the decrease in ethanol concentration, which leads to a decrease in the internal and external osmotic pressure of the composite hydrogel, resulting in a decrease in the kinetic factors for it to complete the response behavior. In 25% and 50% ethanol solutions by volume, the composite hydrogel can complete the transparent-opaque optical change process within 5 minutes, but cannot restore transparency in these solvents. This may be because in low-concentration ethanol, water molecules cannot diffuse in time, thereby causing light scattering, causing the composite hydrogel to always be in an opaque state. This experiment proves that not only can the optical change process be controlled by the contact time between the solvent and the material, but the optical state of the composite hydrogel can also be controlled by controlling the solvent concentration. In addition, the present invention also studied dichloromethane (DCM), ethyl acetate (EA), ethylene glycol (EG), dimethyl sulfoxide (DMSO), methanol (MeOH) and n-hexane (n-Hexane) as solvents to induce the optically adjustable behavior of 5% Ad-PNIPAm gel. The results are shown in Figure 4 As shown in b. First, n-hexane, which is immiscible with water and cannot form hydrogen bonds, cannot induce the transmittance change of the composite hydrogel. 5% Ad-PNIPAm gel cannot induce optical changes after being immersed in n-Hexane for more than 1500 minutes, and it cannot induce optical changes in the composite hydrogel after being immersed in water again. Secondly, DMSO, MeOH and EG, which are miscible with water and can form hydrogen bonds, can induce the hydrogel to produce transparent-opaque-transparent optical transition behavior, and the transparent-opaque-transparent optical change process can also occur after being bathed in water again. Among them, methanol has a smaller molecular structure than ethanol, so the time to complete the solvent replacement is shorter (<40min). Although the ethylene glycol molecule has two hydroxyl groups, the viscosity of the solvent itself is relatively large, so the time to complete the solvent replacement is longer (>1500min). Finally, DCM and EA, which are not easily soluble in water but can form hydrogen bonds, can induce the composite hydrogel to undergo transparent-opaque optical changes, but cannot complete the opaque-transparent transition. Initially, DCM and EA penetrated into the composite hydrogel with the help of the huge osmotic pressure difference to form some hydrogen bonds, but the strong hydrophobicity of the outside made it extremely difficult for water molecules to be expelled from the composite hydrogel, resulting in the inability to complete solvent replacement, which caused the composite hydrogel to remain in a state of high turbidity. The study of different solvents inducing optically tunable behavior of Ad-PNIPAm gel can not only further confirm the mechanism of solvent-induced optically tunable behavior of Ad-PNIPAm gel, but also expand the application potential of Ad-PNIPAm gel as an information encryption and decryption tool.
[0075] Figure 5Rheological and optical properties of composite hydrogels as a function of temperature: (a) storage modulus G' and loss modulus G”; (b) apparent viscosity η*; (c) transmittance. Figure 6 (a) A physical picture of the composite hydrogel changing with temperature; (b) Schematic diagram of the mechanism of temperature-responsive hydrogel optical regulation behavior.
[0076] like Figure 5 As shown in Figs. 5a and 5b, the G' of PNIPAm gel with a single network structure is greater than G" in the temperature range of 4-40℃, showing a stable network structure. G', G" and η* of Ad-PNIPAm gel in the temperature range of 4-40℃ all show a trend of first stabilizing, then increasing and finally decreasing with increasing temperature, which is attributed to the structural contraction and rheological changes caused by the temperature responsiveness of Ad-PNIPAm in the composite hydrogel. Among them, the mechanical property transition temperature (T C ) decreases with the increase of Ad-MA grafting degree. Figure 5 As shown in a, the T values of 1% Ad-PNIPAm gel, 3% Ad-PNIPAm gel, and 5% Ad-PNIPAm gel C 29, 24 and 19°C respectively. Figure 5 c Transmittance mutation temperature in UV test (T T ) is close. Taking 3% Ad-PNIPAm gel as an example, combined with Figure 5 and Figure 6 a. In the range of 4-24℃, G', G" and η* hardly change with the temperature, and the macroscopic appearance is a colorless and transparent gel, and the volume does not shrink significantly. In the range of 24-34℃, G', G" and η* increase rapidly, and the 3% Ad-PNIPAm inside the composite hydrogel in this temperature range curls and gradually transforms into a coiled morphology ( Figure 6b). However, the PNIPAm molecular skeleton can still provide good support for the composite hydrogel, and G' is always greater than G", which shows a transition from transparent to opaque on a macroscopic scale, and no obvious volume shrinkage occurs. When the temperature rises from 24°C to 40°C, it gradually approaches the LCST of PNIPAm as the temperature rises. At this time, the PNIPAm molecular chain begins to shrink and curl, which causes a large number of hydrogen bonds to break, resulting in water molecules being squeezed out of the hydrogel network. This process reduces both G' and G" of PNIPAm gel and their curves eventually intersect, which is manifested macroscopically as the collapse of the composite hydrogel structure, causing obvious volume shrinkage. In summary, the temperature-induced optical regulation behavior is also caused by temperature changes in the composite hydrogel skeleton structure. Experimental data show that the encryption temperature of PNIPAm gel exceeds 40°C, which cannot achieve its encryption behavior at room temperature. However, 1% Ad-PNIPAm gel, 3% Ad-PNIPAm gel and 5% Ad-PNIPAm gel can achieve information encryption at 19-34°C (transmittance <1%) and complete decryption at 4°C. Figure 6 As shown in a, taking 1% Ad-PNIPAm gel as an example, the white grid lines at the bottom of the composite hydrogel are clearly visible in the range of 4-29°C, and they become completely blurred when the temperature rises to 34°C (transmittance <1%). And as the degree of Ad-MA grafting in the composite hydrogel increases, the hydrophobicity of the composite hydrogel continues to increase, and the corresponding LCST decreases accordingly, showing good controllability. This type of composite hydrogel has the potential to be used as an information encryption and decryption tool controlled by LCST switching.
[0077] Figure 7 (a) FT-IR spectrum of Ad-PNIPAm gel / β-CD after immersion in β-CD solution; (b) FT-IR spectrum of Ad-PNIPAm gel / β-CD after removal of free β-CD; (c) G' and G" of Ad-PNIPAm gel / β-CD changing with temperature; (d) temperature scanning comparison of composite hydrogel before and after host-guest recognition; (e) host-guest recognition mechanism diagram of Ad-PNIPAm gel / β-CD regulating response behavior.
[0078] like Figure 7 As shown in a, β-CD can easily enter the pore structure of the composite hydrogel under the action of osmotic pressure, so that β-CD can be observed at 1033 cm in the FT-IR spectra of PNIPAm gel, 1% Ad-PNIPAm gel, 3% Ad-PNIPAm gel, and 5% Ad-PNIPAm gel. -1The COC stretching vibration peak at 1033 cm
[57] and its peak intensity is high, indicating that the β-CD content is high at this time. However, after dialysis in deionized water for 48 h, the PNIPAm gel / β-CD -1 The peak at disappears ( Figure 7 b), indicating that the β-CD in the PNIPAm gel is in a free state. In contrast, after the Ad-PNIPAm gel / β-CD was dialyzed in deionized water for 48 h, the FT-IR spectrum showed a 1033 cm -1 The characteristic absorption peak at , indicating that β-CD and the Ad group side chain in Ad-PNIPAmgel form a stable 1:1 host-guest complex through host-guest recognition, such as Figure 7 e described. Figure 7 c It can be seen that the host-guest recognition between β-CD and Ad has an important influence on the T of Ad-PNIPAm gel / β-CD. C It has a significant effect, extending the inflection points of G' and G" of Ad-PNIPAm gel to 39℃, close to that of PNIPAm gel. However, it has almost no effect on the size of G' and G" ( Figure 7 d) This may be due to the complexation of β-CD with the hydrophobic Ad groups in Ad-PNIPAm gel, which reduces the hydrophobicity of Ad-PNIPAm gel and increases its T C value.
[0079] Figure 8 (a) Comparison diagram of the temperature response encryption process of 5% Ad-PNIPAm gel / β-CD and 5% Ad-PNIPAm gel; (b) Comparison diagram of the self-encryption and decryption process of 5% Ad-PNIPAm gel / β-CD and 5% Ad-PNIPAm gel in ethanol.
[0080] like Figure 8 As shown in a, after the host-guest recognition between β-CD and Ad side chains, the hydrophobicity of the Ad-PNIPAm molecular chain weakens, resulting in a decrease in the sensitivity of Ad-PNIPAm gel / β-CD to temperature response. At 24°C, the pattern at the bottom of the 5% Ad-PNIPAm gel almost completely disappears, while the pattern at the bottom of the 5% Ad-PNIPAm gel / β-CD is still clearly visible until the temperature rises to 34°C, when the 5% Ad-PNIPAm gel / β-CD completely covers the pattern. The hydrophobic Ad group is coated by the hydrophobic inner cavity of β-CD through host-guest interaction, resulting in an increase in the apparent hydrophilicity of the temperature-responsive polymer. Such host-guest recognition can not only broaden the encryption temperature of this type of composite hydrogel but also improve its solvent response characteristics. As Figure 8As shown in Figure b, first, 5% Ad-PNIPAm gel can complete encryption in about 1 minute in ethanol, while 5% Ad-PNIPAm gel / β-CD needs to complete encryption within 5 minutes. Secondly, 5% Ad-PNIPAm gel completes the self-decryption process within 68 minutes, while 5% Ad-PNIPAm gel / β-CD always remains encrypted in ethanol solution. Finally, both can complete decryption in water, realizing dynamic reversible cycle of information encryption and decryption. Since the chemical structure of β-CD is a ring structure composed of 7 glucose units connected by α-1,4 glycosidic bonds, this structure makes it more inclined to form hydrogen bonds with water molecules, while it is difficult to form similar interactions in organic solvents such as ethanol. Therefore, part of the structure of 5% Ad-PNIPAm gel / β-CD in ethanol always maintains hydrogen bonding with water, resulting in the inability of water molecules to diffuse in time, and the information is always in an encrypted state. In summary, the host-guest recognition between β-CD and Ad makes the thermal response temperature and solvent response process of the Ad-PNIPAm gel / β-CD controllable, which is an interesting discovery for building a new information processing model. Therefore, the encryption time of information can be maximized by introducing β-CD.
[0081] Comparison of the results of the above embodiments shows that by changing the grafting degree of Ad-MA in Ad-PNIPAm, the hydrophilic-hydrophobic balance of Ad-PNIPAm can be regulated to adjust the stimulus response performance of Ad-PNIPAm gel. With the increase of the grafting degree of the Ad group, the response temperature of Ad-PNIPAm gel gradually decreases, while the solvent response sensitivity gradually increases. When the theoretical grafting degree of the Ad group is 5%, the response temperature of Ad-PNIPAm gel is the lowest, and the self-encryption process can be completed at 19°C (650nm wavelength, transmittance <1%, time <1min), and the self-decryption process can be completed at 4°C (650nm wavelength, transmittance>75%, time <5min). The encryption time is <1min under the induction of anhydrous ethanol (650nm wavelength, transmittance 78%→0.1%). Through the host-guest recognition effect of β-cyclodextrin and Ad group, the information confidentiality time can be extended to the greatest extent, the information encryption and decryption process can be regulated, and the material usage scenarios can be broadened.
[0082] In summary, the present invention introduces adamantane into the PNIPAm side chain in the gel system through free radical polymerization reaction, constructs a temperature and solvent dual-responsive semi-interpenetrating network composite hydrogel (Ad-PNIPAm gel) with host-guest recognition, and makes it a potential information input, encryption and decryption model device. Then, by changing the concentration of ethanol aqueous solution (5%, 25%, 50%, 75% and 100%) and the type of solvent (DCM, EA, EG, DMSO, MeOH and n-Hexane), the encryption and decryption process of the composite hydrogel is regulated, and by introducing the host-guest recognition effect to adjust the hydrophilic and hydrophobic balance of the composite hydrogel network, its reversible and controllable dynamic response is achieved.
[0083] The Ad-PNIPAm gel of the present invention realizes the passive driving of information encryption through the temperature response of the gel model in a room temperature environment, and completes information decryption at a lower temperature (0-4°C). By artificially adding solvents in a low temperature environment, the information is actively driven by the solvent response of the gel model to complete the encryption of the information. Compared with traditional PNIPAm hydrogels, it has a wider temperature response range and a higher solvent response threshold, and can realize information input, encryption and decryption at low temperatures, making the PNIPAm hydrogel information processing model more suitable for real life scenarios, so that it can be widely used in the field of encryption / decryption.
[0084] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0085] The above is a detailed introduction to a temperature-solvent dual-response information processing hydrogel with host-guest recognition and regulation, a preparation method and its application in information encryption / decryption provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a temperature-solvent dual-responsive information processing hydrogel with host-guest recognition regulation, characterized in that The method comprises the following steps: S1. Synthesis of Ad-PNIPAm: N-isopropylacrylamide (NIPAM), 2,2-azobisisobutyronitrile (AIBN) and 2-methyl-2-adamantyl methacrylate (Ad-MA) were mixed in solvent 1, with a molar ratio of Ad-MA to NIPAM being 1%-8%, and the mixture was flushed with nitrogen and stirred at 60°C±5°C for 20h-24h under a nitrogen atmosphere. Subsequently, solvent 2 was added to the above solution, and the mixture was stirred at 50°C±5°C until crystals precipitated. The mixture was filtered while hot to obtain white powdery Ad-PNIPAm. Repeat the crystallization process to purify the product; finally, dry the purified Ad-PNIPAm under vacuum at 55°C ± 5°C for 24h-30h; S2. Preparation of Ad-PNIPAm gel: At 5°C, Ad-PNIPAm and NIPAM were fully dissolved in water, and appropriate amounts of N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) were added, and stirred vigorously to form a uniform solution. Tetramethylethylenediamine (TEMED) was added to the above solution and mixed evenly. The solution was allowed to stand for crosslinking for more than 24 hours at a temperature range of 0 to 4°C to obtain a semi-interpenetrating composite hydrogel Ad-PNIPAm gel, which was stored at 4°C. S3. Ad-PNIPAm gel / β-CD based on host-guest recognition: Multifunctional Ad-PNIPAm gel / β-CD was prepared through the host-guest recognition between β-CD and Ad; The Ad-PNIPAm gel was immersed in a β-cyclodextrin (β-CD) solution for 8 h to 9 h, and the formed composite hydrogel was taken out and dialyzed to remove the free β-CD in the composite hydrogel to obtain pure Ad-PNIPAm gel / β-CD.
2. The preparation method according to claim 1, characterized in that: The molar ratio of NIPAM, AIBN and Ad-MA described in S1 is 80 mmol: 0.24 mmol: 0.8 mmol to 4.0 mmol.
3. The preparation method according to claim 1, characterized in that: The mass ratio of Ad-PNIPAm to NIPAM described in S2 is 1:0.2 to 1:0.
5.
4. The preparation method according to claim 1, characterized in that: The mass ratio of Ad-PNIPAm to MBA and TEMED in S2 is 2:0.05:0.04~2:0.2:0.16; the mass ratio of MBA to APS is 3:
1.
5. The preparation method according to claim 1, characterized in that: The mass concentration of the β-CD solution described in S3 is 1.0% to 4.0%.
6. The preparation method according to claim 1, characterized in that: The dialysis conditions in S3 were: dialysis in deionized water for 48 h in a dialysis bag with a molecular weight cutoff of 8,000.
7. The preparation method according to claim 1, characterized in that: Solvent 1 and solvent 2 are independently selected from one or more of tetrahydrofuran, n-hexane and diethyl ether.
8. A temperature-solvent dual-response information processing hydrogel prepared by the preparation method according to claim 1.
9. An application of the temperature-solvent dual-response information processing hydrogel according to claim 8 in information encryption / decryption under the regulation of host-guest recognition.
10. The use according to claim 9, characterized in that: The application includes using the temperature-solvent dual-response information processing hydrogel to prepare an information processing hydrogel model device for host-guest recognition regulation.